2022
DOI: 10.1177/16878132221102647
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of heat transfer enhancement using ferro-nanofluids (Fe3O4/water) in a heated pipe under the application of magnetic field

Abstract: Different volume concentrations (1.2, 0.6, 0.3 wt%) of Fe3O4/water nanofluids and for different Reynolds number (Re) varying from 2180 to 9160 were used experimentally. The aim of work is to study the effect of applying various magnetic field intensity 15.1, 30.3, 45.5 mT on heat transfer enhancement in a horizontal pipe heated with constant heating flux of 420 W. Results showed that Nusselt number (Nu) increases with increasing Re for the nanofluids and water regardless the presence or absence of the magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…Like Sharma et al [60], Asirvatham et al [69], Meyer et al [88], Wusiman et al [94], Selvam et al [129], and Saxena et al [135], Demirkir and Ertürk [154] observed that the transition from laminar to turbulent flow occurred at lower Re number with NPs concentration increase. Ebaid et al [155] observed an almost 17% increase in the Nu number with an increase in NPs concentration compared to base fluid for turbulent flow. Siddiqi et al [156] determined that for the same concentration of NPs, the average HTC decreased from a maximum of about 29% by more than half with a doubling of the tube diameter.…”
Section: Characteristics Of the Conducted Researchmentioning
confidence: 98%
“…Like Sharma et al [60], Asirvatham et al [69], Meyer et al [88], Wusiman et al [94], Selvam et al [129], and Saxena et al [135], Demirkir and Ertürk [154] observed that the transition from laminar to turbulent flow occurred at lower Re number with NPs concentration increase. Ebaid et al [155] observed an almost 17% increase in the Nu number with an increase in NPs concentration compared to base fluid for turbulent flow. Siddiqi et al [156] determined that for the same concentration of NPs, the average HTC decreased from a maximum of about 29% by more than half with a doubling of the tube diameter.…”
Section: Characteristics Of the Conducted Researchmentioning
confidence: 98%
“…To synthesize the Fe 3 O 4 nanoparticles, Ebaid et al 26 dissolved 16 g of ferrous-chloride-tetrahydrate (FeCl 2 . 4H 2 O, 99.0%, Fischer) in 300 ml of deoxygenated deionized water and 32 g of ferric-chloride-hexahydrate (FeCl 3 .6H 2 O, 99.0%, Alpha Chemika) in 400 ml of deoxygenated deionized water separately, as shown in Figure 1(a).…”
Section: Preparation Of Nanofluidmentioning
confidence: 99%
“…Previous research into solar PV cooling using nano-fluids has focused on those made with metal, metal-oxide, and silicon carbide nanoparticulate inclusions. Ebaid et al 26 investigated the enhancement of heat transfer using water-based magnetite-nano-fluids in a heated pipe. The results showed that the thermal transfer performance of Fe 3 O 4 /water nano-fluid is significantly affected by the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian ini didasarkan dari penelitian sebelumnya [5] yang dilakukan pada skala laboratorium dengan mencampurkan 8 g besi klorida tetrahidrat (FeCl2.4H2O) dalam 150 mL air asam terdeoksigenasi dan 16 g besi klorida heksahidrat (FeCl3.6H2O) dalam 200 mL air asam terdeoksigenasi yang dilarutkan secara terpisah dan kemudian dipanaskan pada suhu 70 -80 o C. Setelah nanopartikel Fe3O4 terbentuk kemudian endapan disaring dengan kertas saring dan dicuci beberapa kali dengan akuades dan etanol hingga pH netral. Dari prosedur tersebut diketahui bahwa pada proses produksi Fe3O4 membutuhkan sistem pemanasan.…”
Section: Pendahuluanunclassified
“…Pada proses pembuatan nanopartikel Fe3O4 dalam pelaksanaannya merujuk pada penelitian yang sebelumnya telah dilakukan oleh Ebaid [5] dimana tahap yang dilakukan yaitu mencampurkan 8 g besi klorida tetrahidrat (FeCl2.4H2O) dalam 150 mL air asam terdeoksigenasi dan 16 g besi klorida heksahidrat (FeCl3. (2)…”
Section: Metode Penelitian 21 Pembuatan Nanopartikel Fe3o4unclassified